Influence of different light curing units on the bond strength of indirect resin composite restorations - Veridiana Camilotti; Patricia Grau Grullón; Márcio José Mendonça; Paulo Henrique Perlatti D'Alpino; João Carlos Gomes (Sociedade Brasileira de Pesquisa Odontológica, 2008)
The aim of this study was to evaluate the influence of different light sources on the bond strength of indirect resin composite restorations cemented with a dual-cure resin cement. The superficial dentin of human third molars was exposed and acid-etched and an adhesive system was applied (Single Bond 2). Four-mm-thick indirect resin composite restorations (Gradia) were fabricated and cemented using a dual-cure resin cement (Rely X). Four light sources were used to polymerize the cement: QTH - Optilux 401; LED1 - L.E.Demetron 1; LED2 - Optilight CL; and LED3 - Ultralume 5. The teeth were stored for 24 h and then sectioned, yielding stick-shaped specimens for each group with a bonded area of 1.0 mm². The specimens were then tested in a universal testing machine, at a crosshead speed of 1 mm/min. Data were analyzed using ANOVA. Bond strength mean values were: QTH: 22.5 (± 8.4); LED1: 22.7 (± 9.4); LED2: 21.4 (± 10.2); and LED3: 27.3 (± 13.8). No statistically significant difference was observed among the experimental groups. The bond strength values when the cement was polymerized using different LED lights were equivalent to the values when the QTH light was used. It can be concluded that the variety of light sources used in the present study did not influence the bond strength of indirect resin composite restorations cemented with a dual-cure resin cement.